Regional Economic Outlook, May 2018, Europe : Managing the Upswing in Uncertain Times. (Regional Economic Outlook, 2018)
Europe continues to enjoy a strong growth spurt. Growth has firmed up in many European economies and the forecast is for more of the same. Real GDP increased by 2.8 percent in 2017, up from 1.8 percent in 2016. The expansion is largely driven by domestic demand, with investment increasingly contributing. Credit growth has finally picked up, which is helping Europe's banks to rebuild profitability. While leading indicators have recently begun to ease, they remain at high levels. Accordingly, the forecast is for growth to stay strong, reaching 2.6 percent in 2018 and 2.2 percent in 2019. Amid the good times, however, fiscal adjustment and structural reforms efforts are flagging.